Turbulence measurements in the northern gulf of Mexico: Application to the Deepwater Horizon oil spill on droplet dynamics. (March 2016) - Wang, Zhankun; DiMarco, Steven F.; Socolofsky, Scott A.
Abstract: An integrated observational field effort that makes simultaneous and collocated measurements of turbulence and fine-scale parameters has been conducted near the Deepwater Horizon oil spill site in the northern Gulf of Mexico (GOM). Full water column profiles are collected across the continental slope in July 2013. The observational results suggest that strong turbulence is patchy and mostly measured in the thermocline and deepwater when using the buoyancy Reynolds number, Re b =200 criterion, the boundary between weak and strong turbulence. Bottom enhanced turbulence is often seen on the continental slope. Using the ratio of the turbulent velocity scale and the oil droplets rising velocity, we develop criteria for when turbulence will dominate the movement of oil droplets and when turbulence can be ignored. Based on the data collected, for oil droplets with rising velocity greater than 6×10 −3  m s −1, the turbulence effect can be ignored on the continental slope of the northern GOM. For oil droplets with rising speed less than 10 −4  m s −1, their motions will be affected by the turbulent flow at all depths. For oil droplets with rising speed between 10 −4 and 6×10 −3  m s −1, the role of turbulence will depend on the strength of the local turbulence and water stratification. We also relate turbulent velocity to the size and density of oil droplets by estimating the rising velocity of different size oil droplets due to balance between buoyancy and drag force. Droplet size and density difference are the two critical parameters in determining the role of turbulence. Highlights: Turbulence measurements are conducted, for the first time, around the DH spill site. Turbulence in the deepwater of the northern GOM is very patchy and relatively weak. Criteria are developed to determine when turbulence becomes important on oil droplets. Turbulence becomes important on droplets with their rising speed less than 6 mm/s. Two critical physical parameters are turbulent dissipation rate and buoyancy frequency.